2002
DOI: 10.1212/01.wnl.0000032756.14298.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect on mood of subthalamic DBS for Parkinson’s disease A consecutive series of 24 patients

Abstract: A series of 24 consecutive PD patients were prospectively studied prior to and within 6 months postoperatively for mood, motor, and cognitive status to investigate the effects on mood of subthalamic deep brain stimulation (DBS) in PD. In six patients (25%), mood state worsened significantly, and three were transiently suicidal despite clear motor improvement. Caregivers and patients should be educated about the potential impact of this neurosurgical procedure on mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
2
17

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(186 citation statements)
references
References 9 publications
3
164
2
17
Order By: Relevance
“…There is evidence that DBS may also worsen depression and mania, increase apathy, affect emotional lability, and increase the risk of suicide (Berney et al, 2002;Doshi et al, 2002;Okun et al, 2003Okun et al, , 2009Funkiewiez et al, 2004;Smeding et al, 2005Smeding et al, , 2006Drapier et al, 2008;Voon et al, 2008). Mood problems are more common in patients treated with STN-DBS than those treated with GPi-DBS Follett et al, 2010;Moro et al, 2010;Bronstein et al, 2011).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…There is evidence that DBS may also worsen depression and mania, increase apathy, affect emotional lability, and increase the risk of suicide (Berney et al, 2002;Doshi et al, 2002;Okun et al, 2003Okun et al, , 2009Funkiewiez et al, 2004;Smeding et al, 2005Smeding et al, , 2006Drapier et al, 2008;Voon et al, 2008). Mood problems are more common in patients treated with STN-DBS than those treated with GPi-DBS Follett et al, 2010;Moro et al, 2010;Bronstein et al, 2011).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…In addition to improving motor function, some studies have also found DBS to be associated with improvements in mood and depression [40,41,42]. The results of these studies are equivocal, however, as some reports have demonstrated adverse reactions, including significant worsening of depressive symptoms and suicidal ideation [41,43,44] and inducement of mania [45,46,47]. In addition, a randomized, controlled trial of Qigong exercise showed decreases in depression scores in both the control and treatment group, although those in the treatment group did experience a greater improvement in motor symptoms [48].…”
Section: Depression and Parkinson's Diseasementioning
confidence: 99%
“…The resulting signs and symptoms of inappropriate stimulation may be recognized when they differ from the condition being treated by DBS. A variety of negative effects have been described, including depression, 13 suicidality, 14 apathy, 15 mania, 16 anxiety, 17 hypersexuality, 18 and aggressiveness. 19 These symptoms generally occur soon after adjustment of the DBS and thus may occur months to years after implantation.…”
Section: Stimulation Side Effectsmentioning
confidence: 99%